Isolation and characterization of monoclonal antibodies directed against subunits of human RNA polymerases I, II, and III. - Jones, E; Kimura, H; Vigneron, M; Wang, Z; Roeder, R; Cook, P (2000)
Human nuclei contain three different RNA polymerases: polymerases I, II, and III. Each polymerase is a multi-subunit enzyme with 12-17 subunits. The localization of these subunits is limited by the paucity of antibodies suitable for immunofluorescence. We now describe eight different monoclonal antibodies that react specifically with RPB6 (also known as RPA20, RPB14.4, or RPC20), RPB8 (RPA18, RPB17, or RPC18), RPC32, or RPC39 and which are suitable for such studies. Each antibody detects one specific band in immunoblots of nuclear extracts; each also immunoprecipitates large complexes containing many other subunits. When used for immunofluorescence, antibodies against the subunits shared by all three polymerases (i.e., RPB6, RPB8) gave a few bright foci in nucleoli and nucleoplasm, as well as many fainter nucleoplasmic foci; all the bright foci were generally distinct from speckles containing Sm antigen. Antibodies against the two subunits found only in polymerase III (i.e., RPC32, RPC39) gave a few bright and many faint nucleoplasmic foci, but no nucleolar foci. Growth in two transcriptional inhibitors-5, 6-dichloro-1-beta-d-ribofuranosylbenzimidazole and actinomycin D-led to the redistribution of each subunit in a characteristic manner.